Effect of HIV Infection on Human Papillomavirus Types Causing Invasive Cervical Cancer in Africa. (1st November 2016) - Clifford, Gary M.; de Vuyst, Hugo; Tenet, Vanessa; Plummer, Martyn; Tully, Stephen; Franceschi, Silvia
Abstract : Objectives: HIV infection is known to worsen the outcome of cervical human papillomavirus (HPV) infection and may do so differentially by HPV type. Design: Twenty-one studies were included in a meta-analysis of invasive cervical cancers (ICC) among women infected with HIV in Africa. Method: Type-specific HPV DNA prevalence was compared with data from a similar meta-analysis of HIV-negative ICC using prevalence ratios (PR). Results: HPV detection was similar in 770 HIV-positive (91.2%) and 3846 HIV-negative (89.6%) ICC, but HIV-positive ICC harbored significantly more multiple HPV infections (PR = 1.75, 95% confidence intervals: 1.18 to 2.58), which were significantly more prevalent in ICC tested from cells than from biopsies. HPV16 was the most frequently detected type in HIV-positive ICC (42.5%), followed by HPV18 (22.2%), HPV45 (14.4%), and HPV35 (7.1%). Nevertheless, HIV-positive ICC were significantly less frequently infected with HPV16 than HIV-negative ICC (PR = 0.88, 95% confidence intervals: 0.79 to 0.99). Other high-risk types were significantly more prevalent in HIV-positive ICC, but only for HPV18 was there a significantly higher prevalence of both single and multiple infections in HIV-positive ICC. Increases for other high-risk types were primarily accounted for by multiple infections. The proportion of HPV-positive ICC estimated attributable to HPV16/18 (71.8% in HIV positive, 73.4% in HIV negative) or HPV16/18/31/33/45/52/58 (88.8%, 89.5%) was not affected by HIV. Conclusions: HIV alters the relative carcinogenicity of HPV types, but prophylactic HPV16/18 vaccines may nevertheless prevent a similar proportion of ICC, irrespective of HIV infection.